2009
DOI: 10.1016/j.neuron.2009.10.020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Potentiate Neural Development

Abstract: MicroRNAs (miRNAs) are endogenously expressed noncoding RNAs that regulate mRNA expression. In vertebrates, more distinct miRNAs are expressed in the brain than in any other tissue, where they are hypothesized to function in neural development. Recent reports describing the effects of specific miRNAs during development, and studies employing miRNA depletion as neural commitment proceeds in the embryo, support a requisite role for miRNAs in cell-fate decisions and provide clues to their function in other aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
220
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(224 citation statements)
references
References 66 publications
2
220
0
2
Order By: Relevance
“…Several studies have suggested that microRNAs contribute to the establishment and maintenance of synaptic plasticity in developing and mature neurons (1,3,25,26). MicroRNAs regulated by neuronal activity are particularly suited for this role.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that microRNAs contribute to the establishment and maintenance of synaptic plasticity in developing and mature neurons (1,3,25,26). MicroRNAs regulated by neuronal activity are particularly suited for this role.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to translational inhibition or mRNA degradation, reducing the production of hundreds of proteins (6). There is evidence indicating that miRNAs expressed in the brain are involved in neuronal development, survival and apoptosis (7). β-site amyloid precursor protein-cleaving enzyme1 (BACE1), a rate-limiting enzyme involved in the production of Aβ, is important in the pathogenesis of AD (8).…”
Section: Introductionmentioning
confidence: 99%
“…42 Remarkably, miR-185 expression in the present study was particularly pronounced in these brain regions. As microRNAs play an important role in cortical and cerebellar development, 9 prominent miR-185 expression in the developing cortical plate and the cerebellum may be related to 22q11.2DS brain abnormalities. 38,39,42 Gene-based analysis of MIR185 and its predicted target genes revealed no individual or gene-wide association between schizophrenia and common variants at the MIR185 locus per se.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are small noncoding RNAs that control the translation of target messenger RNAs (mRNAs). Accumulating evidence suggests that microRNAs contribute to the basic mechanisms underlying brain development and plasticity, 9,10 thus suggesting their possible involvement in the pathogenesis of several psychi atric disorders, 11 including schizophrenia. 12 This hypothesis is supported by a large genome-wide association study (GWAS) of schizophrenia conducted by the Psychi atric Genomics Consortium (PGC).…”
Section: Introductionmentioning
confidence: 99%